STUDY OF THE PROCESS OF SAMPLE REFINING AND DEODORIZATION OF SUNFLOWER AND SOYBEAN OILS (Innovative Technologica: Methodical Research Journal, 2021)
In our study, it was found that increasing the duration of the deodorization process of sunflower and soybean oil leads to a decrease in the acid number, color and peroxide content of the deodorized oil. The deodorization process lasted 85 and 90 min, with an acid count of 0.3 and 0.25 mg KOH / g, an iodine color of 8 and 6 mg, and a peroxide count of 4 mmol of active oxygen / kg. formed. In the process of refining sunflower oil obtained by extraction, the concentration of alkaline solution was 150 g / l, and the excess was 30%, the yield of refined sunflower oil was 94.3%, acidity 0.18 mg KOH, color 25 mg iodine.